Point mutation analysis of the PBP2B (penicillin binding protein) gene in penicillin resistant Streptococcus pneumoniae strains - Nga, Do Thanh; Chuong, Nguyen Hoang; Quan, Thai Ke; Thuy Duong, Ho Huynh (Academia Journal of Biology, 2015)
We amplified three fragments (2B1, 2B2, 2B3) corresponding to the transpeptidase encoding region of pbp2b gene in 20 penicillin-resistant strains of S. pneumoniae isolated from clinical samples. The fragments were then analysed by SSCP (Single Strand Conformation Polymorphism) electrophoresis. We identified seven SSCP electrophoretic patterns of 2B1, four of 2B2 and five of 2B3 fragments. This high variation in electrophoretic mobility of these fragments shows the great genetic variation of the studied region. The sequencing of these fragments will confirm our results.